Immune stimulatory effect of Nigella sativa in healthy animal models: a systematic review and meta-analysis - Alsalahi, Abdulsamad; Maarof, Nian N.N.; Alshawsh, Mohammed A.; Aljaberi, Musheer A.; Qasem, Mousa A.; Mahuob, Abdulaleem; Badroon, Nassrin A.; Mussa, Ebthag A.M.; Hamat, Rukman A.; Abdallah, Atiyah M. (Elsevier, 2024)
The immune-modulatory effects of black seeds (Nigella sativa seeds, NSS) are well documented, but the overall in vivo impact of this important natural medicinal product on immune system function has yet to be established. Here we systematically reviewed and meta-analyzed the effects of NSS on humoral [serum titers of immunoglobulins including IgG, IgM, anti-Newcastle virus disease (anti-NDV), and sheep red blood cell antigen (anti-SRBC)] and cellular immunity [total white blood cell (WBC) count and percentages of monocytes, lymphocytes, basophils, neutrophils, and eosinophils] in healthy animals. The PubMed, ScienceDirect, Web of Science, and Scopus databases were searched according to predefined eligibility criteria. Meta-analyses were performed to estimate the final effect size using RevMan software. Seventeen animal studies were eligible for analysis. For humoral immunity, the overall pooled effect size (ES) of NSS on serum titers of IgM and anti-NVD antibodies was not significantly different [mean difference (MD) 75.27, 95% CI: −44.76 to 195.30, p = 0.22 (I2 = 89%, p = 0.003), and −0.01, 95% CI: −0.27 to 0.25, p = 0.94 (I2 = 74%, p = 0.02), respectively]. However, NSS significantly increased serum titers of IgG and anti-SRBC antibodies [MD 3.30, 95% CI: 2.27 to 4.32, p = 0.00001 (I2 = 0%, p = 0.97), and 1.15, 95% CI: 0.74 to 1.56, p = 0.00001 (I2 = 0%, p = 0.43), respectively]. For cellular immunity, the ES of NSS on WBCs, monocytes, and lymphocytes were not significantly different [MD 0.29, 95% CI: −0.55 to 1.13, p = 0.50, (I2 = 14%, p = 0.32), - 0.01, 95% CI: −0.45 to 0.44, p = 0.97 (I2 = 0%, p = 0.77), and 4.73, 95% CI: −7.13 to 16.59, p = 0.43, (I2 = 99%, p = 0.00001), respectively]. In conclusion, black seeds enhance humoral immunity in healthy animals but do not affect cellular immunity.